Serum Calretinin as a Biomarker in Malignant Mesothelioma - Cita Zupanc (MDPI AG, 2021)
The early diagnosis of malignant mesothelioma (MM) could improve the prognosis of MM patients. To confirm an MM diagnosis, an immunohistochemical analysis of several tumor tissue markers, including calretinin, is currently required. Our aim is to evaluate serum calretinin as a potential biomarker in asbestos-related diseases, especially in MM. Our study includes 549 subjects: 164 MM patients, 117 subjects with asbestosis, 195 subjects with pleural plaques and 73 occupationally asbestos-exposed subjects without asbestos-related diseases. The serum calretinin concentration was determined with a commercially available enzyme immunoassay. Data on the soluble mesothelin-related peptides (SMRP) concentration are available from previous studies. MM patients had a significantly higher calretinin concentration than subjects without disease, subjects with pleural plaques or subjects with asbestosis (all p < 0.001). The histological type was significantly associated with serum calretinin: patients with sarcomatoid MM had lower calretinin than patients with the epithelioid type (p = 0.001). In a ROC curve analysis, the area under the curve for calretinin concentration predicting MM was 0.826 (95% CI = 0.782–0.869; p < 0.001). At the cutoff value of 0.32 ng/mL, sensitivity was 0.683, while specificity was 0.886. The combination of calretinin and SMRP had the highest predictive value. Calretinin is a useful biomarker that can distinguish MM from other asbestos-related diseases and could, therefore, contribute to an earlier non-invasive diagnosis of MM.